Balance and Core Stabilization Training with Eyes Open Versus Eyes Closed in Young Football Players - Rilind Obertinca; Vilma Dudonienė; Jūratė Požerienė (Lithuanian Sports University, 2019)
Background. Core stability (or core strengthening) has become a well-known fitness trend that has started transcending into sports medicine. It has become a common practice to incorporate balance tasks into the training program for athletes who want to improve performance and prevent injuries. Hypothesis. We suggest that core stabilization and balance training with closed eyes will be more effective than training with open eyes. The aim of the study was to evaluate the effect of core stabilization training with open eyes versus closed eyes on balance and stability of young football players. Methods. Fourteen healthy young football players aged 10-12 years were assessed for pre and post core stabilization training using two balance tests: Stork Balance Test (SBT) and Modified Star Excursion Balance Test (mSEBT), and one test for core stability ‒ McGill Core Stability Test (MCST). The intervention included twelve twenty-minute training sessions each of them involved six core strengthening exercises. One group performed exercises with open eyes, and another with eyes closed. Results. Core stability exercises with eyes closed as well as the same exercise done with eyes open insignificantly improved dynamic balance and core stability, but significantly improved the static balance of the subjects. Conclusion. After applying training with closed eyes as well as eyes open, core stability and balance of young football players increased insignificantly. There were no significant differences in core stability and balance training between training with eyes open and eyes closed. Keywords: core stabilization training, balance, open eyes, closed eyes.